2002
DOI: 10.1093/nar/gkf567
|View full text |Cite
|
Sign up to set email alerts
|

Complex formation of the neuron-specific ELAV-like Hu RNA-binding proteins

Abstract: Hu proteins are RNA-binding proteins that are the vertebrate homologs of Drosophila ELAV, and are implicated in stabilization or enhanced translation of specific mRNAs with AU-rich elements (AREs) in the 3'-untranslated region. Here, using the yeast two-hybrid system, we show that neuron-specific Hu proteins can interact with themselves. Immuno precipitation assays demonstrated that the interaction between Hu proteins occurs in mammalian cells and is strongly enhanced in the presence of cellular RNA. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 44 publications
(30 reference statements)
3
77
1
Order By: Relevance
“…Accordingly, we observed reduced binding of neuronal Hu proteins to the ARE using various binding assays. In addition to decreased HuD expression, the observed decrease in HuD binding may also result from post-translational modification of HuD, or from interactions with other RNA-binding proteins or structural proteins (Kasashima et al, 1999(Kasashima et al, , 2002Pascale et al, 2004). For instance, during neuronal differentiation, HuD binding activity can be controlled by the protein kinase C signaling pathway (Mobarak et al, 2000;Pascale et al, 2005) or through methylation by the methyltransferase CARM1 (coactivator-associated methyltransferase 1) (Fujiwara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we observed reduced binding of neuronal Hu proteins to the ARE using various binding assays. In addition to decreased HuD expression, the observed decrease in HuD binding may also result from post-translational modification of HuD, or from interactions with other RNA-binding proteins or structural proteins (Kasashima et al, 1999(Kasashima et al, , 2002Pascale et al, 2004). For instance, during neuronal differentiation, HuD binding activity can be controlled by the protein kinase C signaling pathway (Mobarak et al, 2000;Pascale et al, 2005) or through methylation by the methyltransferase CARM1 (coactivator-associated methyltransferase 1) (Fujiwara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was observed only when HuR was overexpressed, which may indicate that the activity of HuR depends on the formation of multimeric complexes on its RNA target. In fact, it has been shown recently that Hu proteins can multimerize and retain their RNA binding properties in mammalian cells (60).…”
Section: Cd83 Mrna Contains a Defined Hur-bindingmentioning
confidence: 99%
“…These included HuR, a member of the Drosophila ELAV family, and poly(C)-binding protein (CP1) (27). Both HuR and HuD are known to bind to AU-rich elements in the 3Ј-UTR and to stabilize mRNA (30). Studies on TNF-␣ production in macrophages found that two proteins (TIA-1 (T cell intracellular antigen) and TIAR) bind to the 3Ј-UTR of mRNA for TNF-␣ and silenced its translation.…”
Section: Identification Of a 23-base Rna Fragment From The 3ј-utr Of mentioning
confidence: 99%